Hydrodynamic insights into the paleobiology of the Ediacaran rangeomorph Fractofusus misrai - Daniel Pérez-Pinedo; Robert Nicholls; Jenna M. Neville; Duncan McIlroy (iScience, 2024)
Summary: The Ediacaran of Newfoundland preserves some of the oldest complex macroscopic communities, several of which are dominated by the fractal-like rangeomorph genus Fractofusus. Here we use computational fluid dynamics and a detailed reconstruction of Fractofusus misrai to document for the first time hydrodynamic phenomena associated with this sediment-reclining organism and its rangeomorph elements that are relevant to interpreting feeding strategies, explain the recently documented rheotropic growth oblique to currents, and provide insights into their impact on the Ediacaran seafloor. Obliquely oriented Fractofusus are common, likely representing a compromise between maximized aspect ratio and minimization of drag. Flow patterns on the upper surface of Fractofusus are consistent with the collection of dissolved and finely particulate nutrients, as well as gas exchange. Fractofusus produce a wake downstream, demonstrating that reclining rangeomorphs had potential to modify sedimentation patterns on the ancient seafloor by potentially allowing deposition of fine-grained sediment.